Pemetaan dan perkembangan dalam penelitian sharia governance: Analisis bibliometrik dan visualisasi jaringan dengan vosviewer - Gunawan, Gunawan (Maliki Interdisciplinary Journal, 2026)
This study aims to map the trends and development of shariah governance research through bibliometric analysis and network visualization using VOSviewer software. The study employed a mixed-method approach, combining quantitative bibliometric analysis and qualitative literature review. Research data were collected from Publish or Perish and Scopus using the keyword “Shariah Governance.” From an initial 1,000 articles, a screening and cleaning process resulted in 490 final samples covering the 2020–2026 period. The findings reveal that publications on shariah governance have developed dynamically, peaking in 2020 and increasing again during 2024–2025. VOSviewer analysis identified nine major clusters representing the intellectual structure of the field, including financial performance, shariah compliance, Islamic banking, shariah audit, ESG, risk management, and board governance. Network visualization demonstrates strong relationships among shariah governance, shariah compliance, and financial performance. Meanwhile, density analysis indicates that studies on the impact of governance on financial performance are already saturated, whereas governance issues in zakat, waqf, and nonprofit institutions remain underexplored. This study contributes as a strategic reference for future research directions and for expanding the implementation of shariah governance in non-banking sectors globally.